Suppressing Vacancy Defects and Grain Boundaries via Ostwald Ripening for High‐Performance and Stable Perovskite Solar Cells. Issue 7 (27th December 2019) - Yang, Yuqian; Wu, Jihuai; Wang, Xiaobing; Guo, Qiyao; Liu, Xuping; Sun, Weihai; Wei, Yuelin; Huang, Yunfang; Lan, Zhang; Huang, Miaoliang; Lin, Jianming; Chen, Hongwei; et al.
Abstract: As one kind of promising next‐generation photovoltaic devices, perovskite solar cells (PVSCs) have experienced unprecedented rapid growth in device performance over the past few years. However, the practical applications of PVSCs require much improved device long‐term stability and performance, and internal defects and external humidity sensitivity are two key limitation need to be overcome. Here, gadolinium fluoride (GdF3 ) is added into perovskite precursor as a redox shuttle and growth‐assist; meanwhile, aminobutanol vapor is used for Ostwald ripening in the formation of the perovskite layer. Consequently, a high‐quality perovskite film with large grain size and few grain boundaries is obtained, resulting in the reduction of trap state density and carrier recombination. As a result, a power conversion efficiency of 21.21% is achieved with superior stability and negligible hysteresis. Abstract : Gadolinium fluoride (GdF3 ) and aminobutanol are introduced for Ostwald ripening in the crystal growth of perovskite to overcome the double dilemma of internal defects and external humidity. A GdF3 ‐ and aminobutanol‐treated perovskite solar cell achieves a power conversion efficiency of 21.21% with good stability and small hysteresis, while the pristine device only shows an efficiency of 18.10%.